Cold‐inducible RNA‐binding protein contributes to intracerebral hemorrhage‐induced brain injury via TLR4 signaling. Issue 6 (13th April 2020) - Zhou, Kai; Cui, Shengtao; Duan, Wei; Zhang, Jianrong; Huang, Jiacheng; Wang, Li; Gong, Zili; Zhou, Yu
Abstract: Introduction: Excessive neuroinflammation aggravates the brain injury caused by intracerebral hemorrhage (ICH), while the upstream mechanisms that initiate neuroinflammation remain unclear. Toll‐like receptor 4 (TLR4) signaling is important to trigger inflammatory responses in ICH, and cold‐inducible RNA‐binding protein (CIRP) has been shown as a novel ligand of TLR4 by recent studies. However, whether the CIRP could trigger the neuroinflammation via activating TLR4 signaling in ICH still needs to be investigated. Methods: Human serum CIRP levels were measured using the ELISA kits. Western blot, FJB staining, brain water content, and neurological deficit scores were used to investigate the roles of CIRP in brain injury caused by ICH. Result: First, we found increased CIRP levels in the blood of patients with ICH when compared to the control individuals, and the ICH patients with mRS > 2 have higher serum CIRP levels in contrast to those with mRS ≤ 2. In the ICH mice, we also found that brain CIRP protein and mRNA levels were also increased after ICH. Furthermore, using the CIRP −/− mice, we found that CIRP −/− mice had less brain damages showing in less FJB + cells, reduced brain water content (BWC) and lower neurological deficit scores (NDS) compared to that in WT mice after ICH. Cytokines including IL‐6, TNF‐α, and IL‐1β from CIRP −/− mice were attenuated after ICH. CIRP −/− mice also exhibited reduced TLR4 expression which was accompanied by the decreased activity of NF‐κB. This suggests that TLR4 signaling might be involved in CIRP‐mediated inflammatory injury possibly via NF‐κB activation after ICH. Conclusion: Our findings suggest that CIRP may activate TLR4 signaling, and further inducing NF‐κB activation to increase the expression levels of cytokines and aggravate inflammatory injury in ICH. Targeting CIRP may be a promising strategy for ICH treatment. Abstract : Understanding the upstream mechanisms that initiate neuroinflammation has the potential to identify targets for intracerebral hemorrhage (ICH) treatment. Our data indicate that CIRP may activate TLR4 signaling to increase the expression levels of cytokines and aggravate inflammatory injury in ICH. This study provides a novel insight into the initial events that triggering neuroinflammation after ICH and a new therapeutic target for ICH treatment.